THE CORRELATION OF SELF EFFICACY TO THE STUDENTS’ SPEAKING PERFORMANCE IN EFL CONTEXT AT UNIVERSITY OF DAYANU IKHSANUDDIN BAUBAU - Suharja Suharja (English Education Department, 2020)
The main purpose of this study was to find out the correlation of students’ self-efficacy and their speaking performance. A self-efficacy questionnaire and a measure of speaking performance tests were administered to 95 learners of Dayanu Ikhsanuddin University. The data analysis revealed that there is a significant correlation between the students’ speaking self efficacy and their speaking performance. The probability value of speaking self efficacy is 0.001. Because p < 0.05 then Ho was rejected and Ha was accepted. It can be concluded that students’ speaking self-efficacy and speaking performance denoted a positive correlation.